Energetic consequences of time‐activity budgets for a breeding seabird. (25th July 2016) - Collins, P. M.; Halsey, L. G.; Arnould, J. P. Y.; Shaw, P. J. A.; Dodd, S.; Green, J. A.
Abstract : We deployed accelerometers on breeding kittiwakes to investigate how they allocate time to different behaviours and what the energetic consequences of variation in time allocation to behaviour might be. We provide evidence for higher energy expenditure in chick‐rearing birds when compared to incubating birds, as well as evidence of behavioural compensation to limit overall energy expenditure. Abstract: How animals allocate their time to different behaviours has important consequences for their overall energy budget and reflects how they function in their environment. This potentially affects their ability to successfully reproduce, thereby impacting their fitness. We used accelerometers to record time‐activity budgets of 21 incubating and chick‐rearing kittiwakes ( Rissa tridactyla ) on Puffin Island, UK. These budgets were examined on a per day and per foraging trip basis. We applied activity‐specific estimates of energy expenditure to the kittiwakes' time‐activity budgets in order to identify the costs of variation in their allocation of time to different behaviours. Estimates of daily energy expenditure for incubating kittiwakes averaged 494 ± 20 kJ d −1 while chick‐rearing birds averaged 559 ± 11 kJ d −1 . Time‐activity budgets highlighted that kittiwakes did not spend a large proportion of their time flying during longer foraging trips, or during any given 24‐h period. With time spent flying highlighted as the driving factor behind elevated energy budgets, this suggests behavioural compensation resulting in a possible energetic ceiling to their activities. We also identified that kittiwakes were highly variable in the proportion of time they spent either flying or on the water during foraging trips. Such variation meant that using forage trip duration alone to predict energy expenditure gave a mean error of 19% when compared to estimates incorporating the proportion of a foraging trip spent flying. We have therefore highlighted that trip duration alone is not an accurate indicator of energy expenditure.